The Relationship Between Geography Education and Education for Sustainable Development Between Disciplinary Knowledge and Education Policy: A Systematic Literature Review - Enzmann, Janna; Lindau, Anne-Kathrin (Journal of Geography Education, 2025)
The relationship between geographical education and Education for Sustainable Development (ESD) is emphasized as a special one in many education policy documents. However, it remains unclear what forms this relationship takes in scientific contributions. Therefore, this article examines the portrayal of the relationship between geographical education and ESD in articles published in German-language geography education research. In a systematic literature review, 108 selected scientific articles were analyzed using qualitative content analysis regarding the presentation of this relationship. The findings reveal that, despite frequent mentions, there has been little in-depth discussion of the relationship between geographical education and ESD within German-language geography education research.
Keywords: Education for Sustainable Development (ESD), disciplinary knowledge, geography education, systematic literature review